Effects of intra-aortic balloon pump on in-hospital outcomes and 1-year mortality in patients with acute myocardial infarction complicated by cardiogenic shock - Fang, Dingfeng; Yu, Dongdong; Xu, Jiabin; Ma, Wei; Zhong, Yuxiang; Chen, Haibo (BMC cardiovascular disorders, 2023)
Background The role of intra-aortic balloon counterpulsation (IABP) in cardiogenic shock complicating acute myocardial infarction (AMI) is still a subject of intense debate. In this study, we aim to investigate the effect of IABP on the clinical outcomes of patients with AMI complicated by cardiogenic shock undergoing percutaneous coronary intervention (PCI). Methods From the Medical Information Mart for Intensive Care (MIMIC)-IV 2.2, 6017 AMI patients were subtracted, and 250 patients with AMI complicated by cardiogenic shock undergoing PCI were analyzed. In-hospital outcomes (death, 24-hour urine volumes, length of ICU stays, and length of hospital stays) and 1-year mortality were compared between IABP and control during the hospital course and 12-month follow-up. Results An IABP was implanted in 30.8% (77/250) of patients with infarct-related cardiogenic shock undergoing PCI. IABP patients had higher levels of Troponin T (3.94 [0.73–11.85] ng/ml vs. 1.99 [0.55–5.75] ng/ml, p -value = 0.02). IABP patients have a longer length of ICU and hospital stays (124 [63–212] hours vs. 83 [43–163] hours, p -value = 0.005; 250 [128–435] hours vs. 170 [86–294] hours, p -value = 0.009). IABP use was not associated with lower in-hospital mortality (33.8% vs. 33.0%, p -value = 0.90) and increased 24-hour urine volumes (2100 [1455–3208] ml vs. 1915 [1110–2815] ml, p -value = 0.25). In addition, 1-year mortality was not different between the IABP and the control group (48.1% vs. 48.0%; hazard ratio 1.04, 95% CI 0.70–1.54, p -value = 0.851). Conclusion IABP may be associated with longer ICU and hospital stays but not better short-and long-term clinical prognosis.